R
riverflowsinyou1
Đề khó nhỉ /.
3) a) $\frac{ax-1}{x-1}+\frac{b}{x+1}=\frac{ax^2+a}{(x-1)(x+1)}$
$\frac{(ax-1)(x+1)+bx-b}{(x-1)(x+1)=\frac{ax^2+a}{(x-1)(x+1)}$
\Rightarrow $a.x^2+ax-x-1+bx-b=ax^2+a$
$ax-x-1+bx-b=a$
$a.(x-1)-1+b(x-1)=a$
\Rightarrow $1-b(x-1)=a.(x-2)$
Ngang đoạn này chịu )
3) a) $\frac{ax-1}{x-1}+\frac{b}{x+1}=\frac{ax^2+a}{(x-1)(x+1)}$
$\frac{(ax-1)(x+1)+bx-b}{(x-1)(x+1)=\frac{ax^2+a}{(x-1)(x+1)}$
\Rightarrow $a.x^2+ax-x-1+bx-b=ax^2+a$
$ax-x-1+bx-b=a$
$a.(x-1)-1+b(x-1)=a$
\Rightarrow $1-b(x-1)=a.(x-2)$
Ngang đoạn này chịu )